A Block Chain-Based Security Sharing Framework with Fine-Grained Access Control for Personal Data (International Journal of Food and Nutritional Sciences, 2022)
Privacy protection and open sharing are important data organizations in the artificial intelligence (AI) stage. “The current solution is divided into a data management distribution platform and users upload their own data to the cloud server for storage and distribution. However, when users upload files to the server, they lose their personal data, and security and privacy become an important issue”. Data encryption and orchestration has almost solved this problem and has acquired new capabilities to protect private data on cloud servers. However, it still relies on the trust of third parties such as cloud service providers (CSPs).“In this paper, we propose a blockchain-based personal information and security system referring to the BSSPD concept, which combines blockchain, ciphertext expert attribute-based encryption (CP-ABE) and Interplanetary File System (IPFS) to solve this problem. In this answer, the data enforcers encrypt the combined data and store it in IPFS, which by definition has many branches. The address and decryption key of the shared data will be encrypted using CP-ABE according to the instructions of the supervisor, and the data owner uses the blockchain to publish the data file and issue the key for the operator's data file. Personal data workers who control access rights can download and identify data. Data owners have full control over access to their data and BSSPD supports deletion of certain user data without affecting others.”To protect the confidentiality of operator data, keywords in ciphertext are used when storing data. We have confirmed the credibility of BBSPD and simulated our theory on the EOS blockchain, proving that our knowledge is necessary. At the same time, we use computational analysis of storage and computational loads to determine the efficiency of BSSPD.